2019
DOI: 10.32598/bcn.9.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of ADHD Subtypes Using Decision Tree on Behavioral, Neuropsychological and Neural Markers

Abstract: Introduction: Attention-Deficit/Hyperactivity Disorder (ADHD) is a well-known neurodevelopmental disorder. Diagnosis and treatment of ADHD can often lead to a developmental trajectory toward positive results. The present study aimed at implementing the decision tree method to recognize children with and without ADHD, as well as ADHD subtypes. Methods: In the present study, the subjects included 61 children with ADHD (subdivided into ADHD-I (n=25), ADHD-H (n=14), and ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The study protocol was registered at PROSPERO (CRD42022340624) and followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline (Figure 1…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was registered at PROSPERO (CRD42022340624) and followed the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) reporting guideline (Figure 1…”
Section: Methodsmentioning
confidence: 99%
“…The third study applied a decision tree algorithm to resting state EEG to classify ADHD subtypes (including all three subtypes, ADHD-I, ADHD-H and ADHD-C) and controls (Rostami et al, 2020). The algorithm used a combination of the Child Behavior Checklist (CBCL), Integrated Visual and Auditory (IVA) test, and spectral power in the delta, theta, alpha and beta bands, as well as TBR.…”
Section: Resultsmentioning
confidence: 99%
“…The algorithm used a combination of the Child Behavior Checklist (CBCL), Integrated Visual and Auditory (IVA) test, and spectral power in the delta, theta, alpha and beta bands, as well as TBR. A perfect classification accuracy (100%) was attained for the categories of ADHD versus controls; the algorithm was also able to discriminate among the three ADHD subtypes with an accuracy of 80.41% (ADHD-C), 84.17% (ADHD-I), and 71.46% (ADHD-H), respectively (Rostami et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that the decision tree model yielded excellent classification accuracy (100%). Also, subtypes of ADHD can be distinguished by key nodes in decision-making rules such as behavioral, neuropsychiatric and electrophysiological parameters ( 28 ). New algorithms based on classical decision tree algorithms, including the ones using alternate decision trees, multi-class alternate decision trees, have been used to construct models based on genomic and magnetic resonance data.…”
Section: Supervised Learningmentioning
confidence: 99%